Mineralization of the Tuwu Porphyry Cu Deposit in Eastern Tianshan, NW China: Insights From In Situ Trace Elements of Chlorite and Pyrite - Tan, Wei; Mao, Qigui; Yu, Mingjie; Sun, Yan; Lv, Xiaoqiang (Frontiers in Earth Science, 2021)
The Tuwu porphyry copper deposit is located on the Dananhu-Haerlik island arc in eastern Tianshan, NW China. Based on geology, petrology, and in-situ trace element studies of pyrite and chlorite, we redefined the characteristics of hydrothermal fluids and the following three mineralization stages: premineralization stage (stage Ⅰ), porphyry metallogenic stage (stage Ⅱ) and superimposed transformation stage (stage Ⅲ). Pyrite stage Ⅰ (Py-I) has the highest Co/Ni ratios, and the precipitation crystallization of chlorite (Chl-I2) has the similar rare earth element distribution patterns with those of volcanic rocks (CQ), indicating intense volcanic hydrothermal activity. The Co/Ni ratios of Py-II1 and Py-II2 (stage Ⅱ) tend to decrease over time. Moreover, the REE distribution patterns of Chl-II have similar LREE enrichment, and the Eu anomalies in Chl-II1, Chl-II2 and Chl-II3 range from positive to negative. The initial ore-forming fluid was mainly magmatic hydrothermal fluid, and with the late-stage addition of meteoric water and continuous sulfide precipitation, the trace element composition of the fluid changed, and the whole system became more oxidizing. Py-III (stage Ⅲ) has the lowest Co/Ni ratios, and the REE distribution pattern of Chl-III is characterized by LREE enrichment. Moreover, the Chl-III shows obvious shear deformation characteristics. The results indicate that the host-rocks experienced intensely superimposed reformation. By combining and integrating our results with the regional evolution processes in the eastern Tianshan, we propose that the Tuwu porphyry deposit has undergone magmatic hydrothermal and metamorphic hydrothermal processes. Volcanism (stage Ⅰ) provided the space and initial conditions for the emplacement of the metallogenic body. With the emplacement of the plagiogranite porphyry (stage Ⅱ), the main copper mineralization occurred in the porphyry and surrounding rock. After porphyry mineralization (stage Ⅲ), regional ductile shearing and collisional compression led to a copper reaction, and its accumulation along the faults formed an ore shoot.